PERSONIFICATION IN MARIAH CAREY’S SONG LYRICS - Angelia Firstnov Siow; , Deane J. Wowor; Rinny Rorimpandey (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
The research is done in order to identify and describe the expressions of personification in Mariah Carey’s selected song lyrics. This study is only focuse on the personification expressions in the song lyrics of popular female singer Mariah Carey. Since there are a lot of albums populariz by Mariah Carey during her singing career, the researcher only took albums that consists of song lyrics with personification use to be the subject of the study This study has conduct in qualitative method or also call descriptive research. In this research, the data were collect from the song lyrics of Mariah Carey. The data is analyzingusing the theory According to Miles and Hubermen (2007: 139-140). Based on the result, thirty personification data has found in Mariah Carey’s song lyrics. Language is fundamental to all social processes, and human do need language to communicate to each other. In social process, there are people who communicate more than the say the use language that indicate meaning more than the language does. This terms called figurative language (Samola and Maru; 2016:1). Figurative languages are used in the song lyrics. Specifically, personification is the figurative langugae found through this study. the function of using personifcation expressions is to beautify or decorate the songlyrics them selves so that it is effective in attracting public and the meaning is beautifully delivered to the song listeners. Language style can be help readers and listeners to better understand a meaning of songs, how composer use words in their lyrics, and how does that mean The composer use personification so that the meaning of the wors use become more touching and beautiful.